Precancerous Markers in the Development of Ovarian Endometrioma (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The article contains fragments of a scientific study aimed at developing prognostic criteria for uterine leiomyoma, the authors studied cancer markers in women of reproductive age. Early diagnosis of uterine leiomyoma contributes to effective conservative and organ-preserving treatment of this disease.